Impact of sleep restriction on affective functioning in adolescents with attention‐deficit/hyperactivity disorder. (10th March 2020) - Becker, Stephen P.; Tamm, Leanne; Epstein, Jeffery N.; Beebe, Dean W.
Abstract : Background: Shortened sleep and affective disturbances are both prevalent in adolescents with attention‐deficit/hyperactivity disorder (ADHD), yet the causal link between these domains has not been examined. This study investigated whether shortened sleep duration is causally linked to affective functioning in adolescents with ADHD. Methods: Participants were 48 adolescents (75% male) aged 14–17 years with ADHD who successfully completed a three‐week sleep protocol using an experimental crossover design. The protocol included a phase stabilization week, followed, in randomized counterbalanced order, by one week of sleep restriction (6.5 hr in bed) and one week of sleep extension (9.5 hr in bed). Sleep was monitored with objective actigraphy, and all participants included in this study obtained ≥1 hr actigraphy‐measured sleep duration during extension compared to restriction. Parents and adolescents provided daily ratings of positive and negative affect during the extension and restriction conditions. Ratings of affect, internalizing symptoms, and emotion regulation were collected at laboratory visits conducted at the end of each week. Results: Both parents and adolescents reported greater depressive symptoms and lower positive affect during restriction compared to extension. Parents also reported greater negative affect and emotion dysregulation among adolescents during sleep restriction than extension. No effects were found for parent‐ or adolescent‐reported anxiety symptoms or for adolescent‐reported emotion regulation or negative affect. Conclusions: Findings from this study provide the first evidence that shortened sleep duration is a causal contributor to the affect and mood disturbances frequently experienced by adolescents with ADHD, particularly as observed by parents. Targeting sleep may be important to reduce affective disturbances in adolescents with ADHD.